Keefektifan Wizer.Me sebagai Media Evaluasi dalam Pembelajaran Bahasa Indonesia pada Teks Cerita Pendek di SMP Negeri 1 Singosari - Hamidah, Latifah Winda; Saputra, Oky Dhani; Abadi, Machrus (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
The study addresses the necessity of fully transitioning curriculum-based learning media to digital formats due to current challenges. Junior high school students often experience monotony with conventional evaluation media, necessitating the introduction of innovative tools. In this context, the research explores the implementation of Wizer.me and assesses its effectiveness in teaching Indonesian short story content at SMP Negeri 1 Singosari. Utilizing a quantitative approach with a pre-experimental intact group comparison design, the study reveals promising results. The initial application of Wizer.me exhibits effectiveness, evident in the noteworthy improvement of the average score in Class IX-A by 9.44 points from their pre-test scores. These findings underscore the potential of digital media applications to enhance learning outcomes in Indonesian language subjects.